2014
DOI: 10.1002/mame.201400098
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Chain‐Extended Poly(hexamethylene carbonate)s and their Block Copolymerization with Poly‐L‐lactide to Synthesize Partly Biobased Thermoplastic Elastomers

Abstract: An oligomer of poly(hexamethylene carbonate) (PHMC) that is synthesized by ester‐exchanging polycondensation of ethylene carbonate and 1,6‐hexanediol is chain‐extended by using diphenyl carbonate as chain extender. The resultant PHMC, dihydroxyl‐terminated, is then subjected to tin‐catalyzed ring‐opening polymerization of L‐lactide to prepare ABA tri‐block copolymers consisting of poly‐L‐lactide (PLLA: A) and PHMC (B), which retain significantly high molecular weights even at increased contents of PHMC. Polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…Figure shows the plots of crystallinity ( X ) as a function of APC content (soft block ratio) for the stereo mixtures and their corresponding single copolymers. The data for the latter are those previously reported . Although the APC contents are slightly different between the stereo mixtures and the single block copolymers, it is clear that the crystallinity is almost inversely proportional to the content of soft blocks.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Figure shows the plots of crystallinity ( X ) as a function of APC content (soft block ratio) for the stereo mixtures and their corresponding single copolymers. The data for the latter are those previously reported . Although the APC contents are slightly different between the stereo mixtures and the single block copolymers, it is clear that the crystallinity is almost inversely proportional to the content of soft blocks.…”
Section: Resultssupporting
confidence: 80%
“…Both PLLA‐PHMC‐PLLA and PLLA‐PHPC‐PLLA triblock copolymers were synthesized by tin‐catalyzed ROP of l ‐lactide in the presence of PHMC and PHPC diols as the initiators, as reported previously . The enantiomeric block copolymers PDLA‐PHMC‐PDLA and PDLA‐PHPC‐PDLA were also prepared likewise by using d ‐lactide as the monomer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16] With this nature in mind, we have demonstrated that PHMC diol can be used as a macroinitiator of the ring-opening polymerization (ROP) of L-lactide to prepare tri-block copolymers comprising poly-L-lactide (PLLA) and PHMC (PLLA-PHMC-PLLA) that have both biobased and CO2-originated characters. [17] Since PHMC is crystalline at ambient temperature, the properties of the PLLA-PHMC-PLLA copolymers may be significantly influenced by the temperature change. In the present study, therefore, we use amorphous PHPC diol as the macro-initiator to obtain similar PLLA-APC block copolymers, and for which the elastomeric properties are evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…The dihydroxyl terminated polymer is then used as a macro-initiator for the subsequent ring-opening polymerization of lactide. A variety of polymers can be used as soft block [16,17,21,27,31,38,41], provided that they have a suitably low glass transition temperature, and that they can be obtained with proper terminal functional groups. Recently, the research focused on the development of fully biobased PLA-containing triblocks copolymers, by employing biorenewable soft blocks, such as amorphous polyhydroxyalkanoates [18,26], polymethide [28] and polyesters derived from castor oil [44].…”
mentioning
confidence: 99%